 # 10th Maths Chapter 3 Algebra Exercise 3.2 Guide

10th Standard Maths Chapter 3 Algebra Samacheer Kalvi Guide Exercise 3.2 Book Back Answers Solutions. TN 10th SSLC Samacheer Kalvi Guide. 10th All Subject Guide – Click Here. Class 1 to 12 All Subject Book Back Answers – Click Here ### 1. Find the GCD of the given polynomials

• (i) x4 + 3×3 – x – 3, x3 + x2 – 5x + 3
• (ii) x4 – 1, x3 – 11×2 + x – 11
• (iii) 3×4 + 6×3 – 12×4 – 24x, 4×4 + 14×3 + 8×2 – 8x
• (iv) 3×3 + 3×2 + 3x + 3, 6×3 + 12×2 + 6x + 12

Solution:
x4 + 3×3 – x – 3, x3 + x2 – 5x + 3
Let f(x) = x4 + 3×3 – x – 3
g(x) = x3 + x2 – 5x + 3 Note that 3 is not a divisor of g(x). Now dividing g(x) = x3 + x2 – 5x + 3 by the new remainder x2 + 2x – 3 (leaving the constant factor 3) we get Here we get zero remainder
G.C.D of (x4 + 3×3 – x – 3), (x3 + x2 – 5x + 3) is (x2 + 2x – 3)

(ii) x4 – 1, x3 – 11×2 + x – 11 (iii) 3×4 + 6×3 – 12×2 – 24x, 4×4 + 14×3 + 8×2 – 8x
4×4 + 14×3 + 8×2 – 8x = 2 (2×4 + 7×3 + 4×2 -4x)
Let us divide
(2×4 + 7×3 + 4×2 + 4x) by x4 + 2×3 – 4×2 – 8x (x3 + 4×3 + 4x) ≠ 0
Now let us divide
x4 + 2×3 – 4×2 – 8x by x3 + 4×2 + 4x ∴ x3 + 4×2 + 4x is the G.C.D of 3×4 + 6×3 -12×2 – 24x, 4×4 + 14×3 + 8×2 -8x
∴ Ans x (x2 + 4x + 4)

(iv) f(x) = 3×3 + 3×2 + 3x + 3 = 3(x3 + x2 + x + 1)
g(x) = 6×3 + 12×2 + 6x + 12
= 6(x3 + 2×2 + x + 2)
= 2 × 3 (x3 + 2×2 + x + 2)
f(x) ⇒ x3 + x2 + x + 1 ### 2. Find the LCM of the given expressions,

• (i) 4x2y, 8x3y2
• (ii) -9a3b2, 12a2b2c
• (iii) 16m, -12m2n2, 8n2
• (iv) p2 – 3p + 2, p2 – 4
• (v) 2×2 – 5x – 3, 4×2 – 36
• (vi) (2×2 – 3xy)2, (4x – 6y)3, 8×3 – 27y3

Solution:
(i) 4x2y, 8x3y2
4x2y = 2 × 2 x2y
8x3y2 = 2 × 2 × 2 x3y2
L.C.M. = 2 × 2 × 2 x3y2
= 8×3 y2

(ii) -9a3b2 = -3 × 3 a3b2
12a2b2c = 2 × 3 × 2a2b2c
L.C.M. = -3 × 3 × 2 × 2 a3b2c
= -36a3b2c

(iii) 16m, -12m2n2, 8n2
16 m = 2 × 2 × 2 × 2 × m
-12m2n2 = -2 × 2 × 3 × m2n2
8n2 = 2 × 2 × 2 × n2
L.C.M.= -2 × 2 × 2 × 2 × 3 m2n2
= -48 m2n2 (v) 2×2 – 5x – 3, 4×2 – 36
2×2 – 5x – 3 = (x – 3)(2x + 1)
4×2 – 36 = 4(x + 3)(x – 3)
L.C.M. = 4(x + 3)(x – 3)(2x + 1)

(vi) (2×2 – 3xy)2 = (x(2x – 3y))2
(4x – 6y)3 = (2(2x – 3y))3
8×3 – 27y3= (2x)3 – (3y)3
= (2x – 3y) (4×2 + 6xy + 9y2)
L.C.M. = 23 × x2 (2x – 3y)3 (4×2 + 6xy + 9y2)